2011
DOI: 10.1016/j.exger.2011.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Life-extending dietary restriction and ovariectomy result in similar feeding rates but different physiologic responses in grasshoppers

Abstract: Dietary restriction (DR) and reduced reproduction each extend life span in many species. Females undergoing DR typically experience a reduction in their fecundity, which raises the question of whether the two treatments are actually extending life span in overlapping ways. Life span in lubber grasshoppers has been shown to be increased by DR, and separately by ovariectomy (OVX). Here, we test the combination of these on life span. If life extension by the two treatments are additive, it would suggest that they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 48 publications
5
29
0
Order By: Relevance
“…As in previous studies (e.g., Drewry et al 2011), body masses for all treatments increased rapidly until about 3 weeks, and continued to increase slowly until a median age of 6 weeks, a time just following the oviposition of the first clutch in fully reproductive individuals (Fig. 3).…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…As in previous studies (e.g., Drewry et al 2011), body masses for all treatments increased rapidly until about 3 weeks, and continued to increase slowly until a median age of 6 weeks, a time just following the oviposition of the first clutch in fully reproductive individuals (Fig. 3).…”
Section: Resultssupporting
confidence: 82%
“…Animals with both ovariectomy and VgRNAi treatment maintained the same feeding levels as the other reduced reproduction groups, indicating that the changes to feeding were not additive. Drewry et al (2011) show that ovariectomy reduces feeding (~40%) and proposed that other ways to reduce reproduction may also decrease feeding as well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that ovariectomized grasshoppers have ~20% greater median life span than sham-operated controls (Hatle et al 2008; Drewry et al 2011). In contrast to other models in which the ovary is missing, ovariectomized grasshoppers continue to make the egg yolk-precursor protein vitellogenin, which accumulates in the hemolymph (Hatle et al 2003).…”
Section: Introductionmentioning
confidence: 99%